Enhanced phenylpyruvic acid production with Proteus vulgaris in fed-batch and continuous fermentation. Issue 2 (17th February 2016) - Coban, Hasan B.; Demirci, Ali; Patterson, Paul H.; Elias, Ryan J.
ABSTRACT: Phenylpyruvic acid is a deaminated form of phenylalanine and is used in various areas such as development of cheese and wine flavors, diagnosis of phenylketonuria, and to decrease excessive nitrogen accumulation in the manure of farm animals. However, reported phenylpyruvic acid fermentation studies in the literature have been usually performed at shake-flask scale with low production. In this study, phenylpyruvic acid production was evaluated in bench-top bioreactors by conducting fed-batch and continuous fermentation for the first time. As a result, maximum phenylpyruvic acid concentrations increased from 1350 mg/L (batch fermentation) to 2958 mg/L utilizing fed-batch fermentation. Furthermore, phenylpyruvic acid productivity was increased from 48 mg/L/hr (batch fermentation) to 104 and 259 mg/L/hr by conducting fed-batch and continuous fermentation, respectively. Overall, this study demonstrated that fed-batch and continuous fermentation significantly improved phenylpyruvic acid production in bench-scale bioreactor production.